1998
DOI: 10.1046/j.1365-2648.1998.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection and retention of nurses

Abstract: The selection and retention of suitable nurses has occupied the thoughts of many people who have a vested interest in maintaining standards and avoiding loss of resources. By drawing conclusions from inadequate findings inappropriate recommendations may be made. In a study that considers the psychological profiles of nurses, it would appear that it is self-esteem and a 'need to be needed' that is a crucial facet of nurses ability to cope with the job of nursing; a job that encourages the characteristics of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…These included stress associated with 'unmet learning needs' and stress associated the clinical setting for these valuable members of our health service at a time when attrition in nursing is so prevalent (Muncey, 1998;Evans, 2001;Deary et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These included stress associated with 'unmet learning needs' and stress associated the clinical setting for these valuable members of our health service at a time when attrition in nursing is so prevalent (Muncey, 1998;Evans, 2001;Deary et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The open-ended question gave participants an opportunity to make comments or suggestions in relation to stress in the clinical environment from their own perspective, focussing within the clinical environment. Student nurses and indeed newly qualified nurses may find themselves in a vulnerable position particularly in new surroundings with new people (Muncey, 1998). As a consequence to finding themselves entering a different organisational culture (Marguis and Huston, 2000), they often are reluctant to tell anyone that they are "not coping" or finding the transition stressful (White, 1996) and are often discouraged to admit that they have experienced stress (Healy and McKay, 2000).…”
Section: Designmentioning
confidence: 99%
“…Stress associated with academic work has been found to be a significant feature of preregistration diploma courses (Lindop 1999), and a perceived unpredictability of academic timetables added to their belief that they were never in control of their work. Muncey (1998) suggested that self‐control is important to mature students with life experience, and that this becomes compromised by diverse demands placed on them.…”
Section: Discussionmentioning
confidence: 99%
“…These early experiences could influence decisions to seek a career within a perceived therapeutic community, but were likely to be a predictive factor in occupational stress. Muncey (1998) argues that if the underlying influence of psychological profiles of nurses on attrition were accepted, then this would necessitate better support services for vulnerable individuals.…”
Section: Introductionmentioning
confidence: 99%